Quantcast i need more help with math please!? - XP Math - Forums
XP Math Home Sign Up FREE! | Sign In | Classroom Setup | Common Core Alignment PDF Version

Go Back   XP Math - Forums > Welcome > Off-Topic Discussion

Reply
 
Thread Tools Display Modes
Old 07-17-2007   #1
Jules
Guest
 
Posts: n/a
Default i need more help with math please!?

what is? FOIL 1. (x+4)(x-2) = 2. (-2x-3)(3-x) =
  Reply With Quote
Old 07-17-2007   #2
Knock N
Guest
 
Posts: n/a
Default

Multiply: First Outter Inner Lastx * x -2x 4x -8
  Reply With Quote
Old 07-17-2007   #3
gabriel070286
Guest
 
Posts: n/a
Default

1. (x + 4) (x - 2) = x*x - 2x + 4x -8= x^2-2x+4x-8 = x^2+2x-82. (-2x-3) (3-x)= -2x* 3 + 2x*x-3*3 + 3*x=-6x+2x^2-9+3x= 2x^2-3x-9
  Reply With Quote
Old 07-17-2007   #4
ehhh....
Guest
 
Posts: n/a
Default

F irstO uterI innerL astu multiply the first numbers or x in parenthesis, the the outer numbers, then the inner, then the lastx^2+4x-2x-8= x^2+2x-8-6x+2x^2-9+3x= 2x^2-3x-9
  Reply With Quote
Old 07-17-2007   #5
♥ Dani
Guest
 
Posts: n/a
Default

FOIL stands for First, Outer, Inner, Last. It's the order you can use to solve those problems.Multiply the first terms in each set of parentheses (in #1, the 2 x's). Then multiply the 2 terms on the outside (in #1 this is the first x and the -2). Then multiply the inner terms (in #1 these are the second x and the 4). Last, multiply the last terms (in #1 it's the 4 and the -2).1. (x + 4)(x - 2) = (first) x^2 (outer) -2x (inner) +4x (last) -8= x^2 - 2x + 4x + 8 __ clean this up a bit by adding like terms.= x^2 + 2x - 8And there you have it. You can do #2 in the same way.(-2x - 3)(3 - x) = (first) -6x (outer) +2x^2 (inner) -9 (last) +3xreorder that a bit... = 2x^2 - 6x + 3x - 9 ... and add like terms.so #2 = 2x^2 - 3x + 9
  Reply With Quote
Old 07-17-2007   #6
blossom
Guest
 
Posts: n/a
Default

1. x2 + 4x - 2x - 8 = x2 + 2x -82. (-2x-3)(-x+3)= 2x2 + 3x - 6x - 9 = 2x2 - 3x - 92x2 meaning 2x squared. Don't know how to make the 2 superscript.
  Reply With Quote
Old 07-17-2007   #7
txmama423
Guest
 
Posts: n/a
Default

foil=multiply the first terms, then the outer, then the inner terms & then the last terms; 1. (x+4)(x-2)=x^2-2x+4x-8(combine like terms now),= x^2+2x-82. (-2x-3)(3-x)= 2x^2-6x+3x-9= 2x^2-3x-9
  Reply With Quote
Old 07-17-2007   #8
febbfish
Guest
 
Posts: n/a
Default

1. For expansion you multiply the terms 1 by 1..(x+4)(x-2) = (x * x) + [x * (-2)] + [(+4) * x] + [(+4) * (-2)] = x^2 + (-2x) + (4x) + (-8) = x^2 - 2x + 4x - 8 = x^2 + 2x - 8Take note of the signs when you open the brackets.2. (-2x-3)(3-x) = [(-2x) * 3] + [(-2x) * (-x)] + [(-3) * 3] + [(-3)* (-x)] = (-6x) + (2x^2) + (-9) + (3x) = -6x + 2x^2 - 9 + 3x = 2x^2 - 3x - 9Remember the sign belongs to the term behind the sign.
  Reply With Quote
Old 07-17-2007   #9
curiosity2414
Guest
 
Posts: n/a
Default

1)(x+4)(x-2)x^2+2x-82)(-2x-3)(3-x)-6x^2-9+2x+3x=-6x^2+6x-9
  Reply With Quote
Old 07-17-2007   #10
calpal2001
Guest
 
Posts: n/a
Default

1. (x + 4) (x - 2) = x^2 +4x - 2x - 8= x^2 + 2x - 8x = -4, 22.(-2x - 3)(3 - x) = -6x - 9 + 3x + 2x^2= -9 - 3x +2x^2= 2x^2 - 3x - 9x = - 3/2 , 3
  Reply With Quote
Reply

Thread Tools
Display Modes

Posting Rules
You may not post new threads
You may not post replies
You may not post attachments
You may not edit your posts

BB code is On
Smilies are On
[IMG] code is On
HTML code is Off

Forum Jump


All times are GMT -4. The time now is 12:32 AM.


Powered by vBulletin® Version 3.8.11
Copyright ©2000 - 2020, vBulletin Solutions Inc.
XP Math